La flora triásica del Grupo El Tranquilo, provincia de Santa Cruz, Patagonia. Parte VI: Ginkgoales (Ameghiniana, 2014)
As part of the systematic study of the flora from El Tranquilo Group, the ginkgoal taxa are revised herein. The following species are considered: Ginkgoiies duioiiii Anderson and Anderson, Ginkgoites patma¡a (Ratte) combo nov., Ginkgodium nathorsti Yokoyama, Ginkgodium sp.; Baiera africana Baldoni, Baiera gillkgoides Shirley; Sphenobaiera argentinae (Kurtz) Frenguelli, Sphenobaiera coronata Anderson and Anderson, Sphenobaiera stormbergensis (Seward) Frenguelli, S. sectina Anderson and Anderson, Sphenobaiera sp. d. s. browllialla Anderson and Anderson, Sphenobaiera sp. d. s. he/vetica Anderson and Anderson, Sphenobaiera sp. A, Sphenobaiera sp. B and Sphenobaiera sp. C from the Cañadón Largo Formation and Ginkgoites waldeckensis (Anderson and Anderson) combo nov. and Ginkgoites sp. 1from the Laguna Colorada Formation.